Queer lives: navigating Singapore's housing landscape - Chng, Glenda Kai Lin (Nanyang Technological University, 2024)
While housing is a basic human right, there has been a global housing shortage issue. In Singapore, the unique public housing policies, combined with conservative Asian values, has resulted in nuanced experiences and novel strategies employed by the queer community in the housing scene. The lack of research in housing challenges within the queer community has prompted us to conduct an exploratory research to investigate the intricate housing decisions of queer individuals in Singapore. This study considers factors such as family dynamics, relationships, financial constraints, and housing policies in relation to the queer community. Drawing on life-course theory and key sociological frameworks, we uncover the strategies employed by queer individuals in navigating familial environments and housing needs. Our findings reveal strategies such as "don't ask, don't tell" approaches to allow for amicable family relations, prolonged stays within familial homes, planned exits and other strategies such as staying with a partner. Through this study, we shed light on the resilience and adaptability of Singaporean queers in navigating the housing scene while maintaining close familial ties. This research not only addresses a significant gap in literature but also emphasises the importance of understanding the complexities of housing decisions within marginalised communities.